2013
DOI: 10.5539/ass.v9n15p130
|View full text |Cite
|
Sign up to set email alerts
|

Language Learning Difficulties among Malaysian Gifted Students

Abstract: Gifted students have unique characteristics and have different ways of thinking and learning. These characteristics affect how they learn a language. This study investigates gifted students' difficulties in English language learning. Data was gathered using semi structured interview with six gifted students of PERMATA Pintar National Gifted Centre. In this study, interview analysis was used to analyze interview transcripts in order to find gifted language learning difficulties among gifted students. An analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
2
2
0
Order By: Relevance
“…Compared with other studies, present study shows similar results (Sparks and Ganschow, 1993). A study which was done among the school students has concluded that, majority of students feels difficulty in learning the subjects, which may be due to teaching methods (Melhem and Isa, 2013) A survey was conducted among people in a university, saying that people who lack self determination and motivation face many problems in academics (Yunus et al, 2013), (Acharya, 2003) Though many studies have done learning disabilities in school students and others, this study aims to evaluate the learning difficulties in dental students (Korhonen, Linnanmäki and Aunio, 2014). Our team has extensive knowledge and research experience that has translated into high quality publications ( The major purpose of this study is to explore detailed information on the difficulties faced by the dental students in learning the subjects and in doing practicals.…”
Section: Introductionsupporting
confidence: 80%
“…Compared with other studies, present study shows similar results (Sparks and Ganschow, 1993). A study which was done among the school students has concluded that, majority of students feels difficulty in learning the subjects, which may be due to teaching methods (Melhem and Isa, 2013) A survey was conducted among people in a university, saying that people who lack self determination and motivation face many problems in academics (Yunus et al, 2013), (Acharya, 2003) Though many studies have done learning disabilities in school students and others, this study aims to evaluate the learning difficulties in dental students (Korhonen, Linnanmäki and Aunio, 2014). Our team has extensive knowledge and research experience that has translated into high quality publications ( The major purpose of this study is to explore detailed information on the difficulties faced by the dental students in learning the subjects and in doing practicals.…”
Section: Introductionsupporting
confidence: 80%
“…It is therefore not a surprise when findings of a study in Malaysia show that despite having gone through six years of learning English in school environment, the learners are still having difficulty in using correct English grammar in their writings (Maros et al, 2007). Similar finding was also gathered from a study on gifted learners who were found facing difficulty in applying grammatical rules in discourse manner (Md Yunus et al, 2013). Even at tertiary level, Yusob (2018) found that experienced lecturers too faced difficulty in teaching and explaining about English grammar to the students.…”
Section: Introductionsupporting
confidence: 57%
“…Therefore, they have to make sure that the students' vocabulary increases. This was supported by Yunus, Sulaiman, Kamarulzaman, and Ishak, (2013) that common difficulties in learning English faced by intelligent students related to speaking English, lack of vocabulary, grammar, and speaking skills are the most difficult to learn. In an environment of people who are not native speakers to speak English it is difficult to be able to speak accurately and smoothly like native speakers (Ting, Mahadhir, & Chang, 2011).…”
Section: Advances In Social Science Education and Humanities Research Volume 461mentioning
confidence: 87%